A study of Developing Guideline for Sangha’s Education - ศิริวรรณ อินถา; วงศ์สุวรรณ นิเวศน์ (Journal of Educational Review Faculty of Education in MCU, 2018)
The objectives of this descriptive research were to study the form of education management in Phrapariyattidhamma Study in Dhamma Section and Pali section suitable to subjects in general education section. The samples used in the study consisted of 26 experts; 16 monks and 10 lay-men. The research instrument was 5-rating scale questionnaire. The study found that Phrapariyattidhamma curriculum in Dhamma Section and in Pali Section should adjusted according to Education Act permitting Buddhist institutes in running education. A suitable form of education management for Phrapariyattidhamma curriculum in Dhamma Section and in Pali Section was to allow monks and novices study Dhamma, Pali and general education together at the same time starting from Matthayom 1 to Ph.D. level. The course subjects that should be provided for monks and novices to study were: foreign languages, Thai language, social study, religion and culture, arithmetic, arts, science, hygiene and physical education, vocation and technology. At the same time, the teaching and learning methods in Dhamma and Pali should be improved in accordance with the modern time. Then the Phrapariyattidhamma curriculum can fulfill the need of learners more and more. Having finished Pathom 6, more children will be interested in ordination and study in temple. Furthermore, the improved curriculum will be implemented in child schools and that will directly result to the prosperity of Buddhism and happiness of learners.